Drug-induced gingival enlargement: Series of cases - Manzur-Villalobos, Isabella; Díaz-Rengifo, Ivan Alejandro; Manzur-Villalobos, Daniella; Díaz-Caballero, Antonio José (Universidad y Salud, 2018)
Introduction: Gingival enlargement (GA) is a benign condition of the oral cavity that is characterized by the excessive growth of the gingiva in mass and volume. This lesion is not only caused by hereditary factors or poor oral hygiene, but also by the intake of medications, including antihypertensive, anticonvulsant and immunosuppressive drugs. Objective: To sensitize the prevention or early care in patients with pathologies that merit the use of antihypertensive and anticonvulsants in conjunction with the dentist, to treat or avoid the drug-induced gingival enlargement (DIGE). Materials and methods: A series of clinical cases of patients with gingival enlargement by various drugs are reported, including Phenytoin, Amlodipine and Nifedipine. Periodontal and gingivectomy hygienic phase measures were applied to obtain better effects. Results: Satisfactory results were obtained with a considerable decrease in DIGE. Conclusions: The integral management is important in conjunction with the treating physician to follow up the drug that can be generating gingival enlargement. It is necessary to employ an initial approach with strategies of periodontal hygiene, and in severe cases and, as last resort, the periodontal surgery with gingivectomy and gingivoplasty.